Legal nature of affatomia - Stanković Miloš (Anali Pravnog Fakulteta u Beogradu)
In Salian and Ripuarian Code affatomia represented a bilateral legal transaction that was aimed at changing of the scoped of heirs determined by the customs, at least insofar being applied in the absence of biological descendants only. However, almost all further similarities in the field cease at this point. The form for using affatomia with Ripuarian Franks was much simpler than the one with the Salian Franks. Unlike the Salian Franks, affatomia could by all odds be used by Ripuarian Franks spouses in determining each other for a heir. Legal nature of the Salian Franks affatomia is most similar to the mancipatio familiae type of will in the Roman law (which does not mean it emerged from this law), while its form in the Ripuarian Code is much closer to testamentary adoption. As with Ripuarian Franks, affatomia seems to have definitely produced legal effects only after the death of the disposant, while its legal effects with the Salian Code performed inter vivos. Contemporary authors are trying to designate the legal nature of legal affairs from the early development of human and legal civilization through modern institutes that represent the completion of their evolutionary path. Taking the inheritance contract of the German or Swiss law, or the future assets donation of the French law, for example, and then comparing them to affatomia and thinx is an anachronism. This is evident by the fact that the legal nature of these ancient Germanic institutes can not be viewed unilaterally, but always through a combination of those institutes which we know today as adoption, gift or mixed donation with retention of different modalities for the transferor or the testator (usually usufruct). In this sense, if we are looking for a inheritance agreement in the Middle Ages, the contract in which a person determines other person for his/her universal or singular successor in the modern sense, we will certainly not find one. However, if within this institute we see bilateral legal transaction whose subject is the future legacy or exactly specified legal issue from legacy, which aims to voluntarily change the law and customs of the established circuit of heirs, who partially performed legal effects among the living, and partly in case of death, the one that differs from the legacy through its irreversibility, we will then find its roots with the Franks and the Langobards, while its first clear shapes and forms we will find as early as XIII century. If we start from this initial premise, bearing in mind that different nations in different historical epochs attained a certain level of cultural, economic and legal emancipation, it is possible to draw another conclusion. It is the fact that disposal of assets in case of death, which meant some form of approval of the one in whose favour assets were disposed (what we would call today a bilateral legal transaction), has always preceded legacy as a unilateral legal transaction. Further on, it means that affatomia and thinx, as well as Morgengabe, can be considered roots in Germanic contractual inheritance law. But if we follow the development of an idea, abstracting the inevitable differences, Babylonian nudunu, Islamic vassijet, donatio mortis causa (from Babylon, through the Spartan and Roman law, to the Mirror of the Saxons), Vergabungen of the Schwabenspiegel, especially the Roman mancipatio familiae last will, can all equally be regarded as the roots of the contractual inheritance.